THE PERCEPTION OF THE GMIM DAMAI BELANG ATEP CONGREGATION ABOUT HEALTHY FAMILIES IN THE CONTEXT OF THE BIBLE: Persepsi Jemaat Gmim Damai Belang Atep tentang Keluarga Sehat dalam Konteks Alkitab - Rafael Wahongan; Tesalonika Jocom; Jecelly Ratag; Alva Tuerah; Yudea Pelle; Vanny Nancy Suoth; Ramli Sarimbangun; Maria Elisa Tulangouw (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This paper explores the meaning of the idea of a healthy family to members of GMIM Damai Belang Atep, as well as how that idea is played out in biblical view, and the things that promote or inhibit it in a Minahasan context. In response to the normative discourses of Christian families in Indonesian theology, this study follows an exploratory qualitative research design with a phenomenological orientation. Semi-structured interviews with a purposely chosen sample of families and special office-bearers were used to collect data, which were analyzed with the help of thematic analysis and contextual theological reflection. The results indicate that congregants identify proper families in terms of relationships and Christ-centered ways. Mutual love and respect, common spiritual disciplines, equal emphasis on spiritual, emotional, and practical needs, and the deliberate impartation of biblical values to children are all related to family health. These beliefs are reflected in everyday activities, family worship, shared prayer, eating together, helping others, and spiritually oriented ways of resolving conflicts, which emphasize calm speaking, controlling oneself, forgiving, and praying. Concurrently, families are experiencing problems such as financial strain, family time, screen addiction, and value system clashes in the external world. The cultural values of Minahasan, most notably mapalus, kinship, and solidarity, are revealed as social capital that can be used to support biblical ideals, although some of the characteristics should be discerned. This paper suggests a contextual model of a healthy family and the necessity of the church to supplement doctrinal teaching with pastoral accompaniment based on families.